Nicotinamide enhances myelin production after demyelination through reduction of astrogliosis and microgliosis - Kaplanis, Stefanos Ioannis; Kaffe, Despoina; Ktena, Niki; Lygeraki, Andriani; Kolliniati, Ourania; Savvaki, Maria; Karagogeos, Domna (Frontiers in Cellular Neuroscience, 2023)
Caloric restriction is the chronic reduction of total caloric intake without malnutrition and has attracted a lot of attention as, among multiple other effects, it attenuates demyelination and stimulates remyelination. In this study we have evaluated the effect of nicotinamide (NAM), a well-known caloric restriction mimetic, on myelin production upon demyelinating conditions. NAM is the derivative of nicotinic acid (vitamin B3) and a precursor of Nicotinamide Adenine Dinucleotide (NAD + ), a ubiquitous metabolic cofactor. Our data shows that NAM enhances both myelination and remyelination ex vivo, while it also induces myelin production after lysolecithin (LPC)-induced focal demyelination ex vivo and in vivo. The increased myelin production is accompanied by reduction in both astrogliosis and microgliosis in vivo. There is no direct effect of NAM on the oligodendrocyte lineage, as no differences are observed in oligodendrocyte precursor cell proliferation or differentiation or in the number of mature oligodendrocytes. On the other hand, NAM affects both microglia and astrocytes as it decreases the population of M1-activated microglia, while in primary cultures of astrocytes, the proinflammatory phenotype is reduced as assayed by the reduction of TNF-α. Overall, we show that the increased myelin production that follows NAM treatment in vivo is accompanied by a decrease in both astrocyte and microglia accumulation at the lesion site. Our data indicate that NAM influences astrocytes and microglia directly, in favor of the remyelination process and by promoting a less inflammatory environment.